Cloning and Characterization of a New Site-Specific Methyl-Directed ElmI Endonuclease Recognizing and Cleaving C5-methylated DNA Sequence 5’-G(5mC)^NG(5mC)-3’ - Chernukhin, V. A. (Acta Naturae, 2016)
Putative open reading frames of MD-endonucleases have been identified in Enterobacteria genomes as a result of the search for amino acid sequences homologous to MD-endonuclease BisI. A highly conserved DNA primary structure of these open reading frames in different genera of Enterobacteria (Escherichia, Klebsiella and Cronobacter) has allowed researchers to create primers for PCR screening, which was carried out on Enterobacteria DNA collected from natural sources. The DNA fragment, about 440 bp in length, was amplified by use of the genomic DNA of a wild E.coli LM N17 strain as a template and was inserted into the pMTL22 vector. Endonuclease activity was detected in an E.coli ER 2267 strain transformed with the obtained construction. A new enzyme named ElmI was purified by chromatographic techniques from the recombinant strain biomass. It was discovered that similarly to BisI this enzyme specifically cleaves the methylated DNA sequence 5’-GCNGC- 3’ before the central nucleotide “N” if this sequence contains two 5-methylcytosines. However, unlike BisI, ElmI more efficiently cleaves this sequence if more than two cytosine residues are methylated.